Recurrent head thump sensations: two cases suggesting a novel headache phenotype - Valença, Marcelo Moraes; Reis, Rita Santana dos; Vasconcelos Junior, Florisvaldo José Morais; Santana, Claudia Cristina de Lira; Souza, Bruno Felipe Novaes de; Andrade, Juliana Ramos de; Peres, Mario Fernando Prieto (Headache Medicine, 2026)
IntroductionParoxysmal cranial sensations without pain are rarely reported and remain poorly characterized within current headache classifications. Although entities such as primary stabbing headache or epicrania fugax are defined by brief, sharp pain, non-painful focal cranial paroxysms are uncommon and understudied. We describe two cases of recurrent, brief, non-painful “head thump” sensations involving the vertex or parietal regions, persisting for over one year, to increase awareness of this atypical sensory phenomenon.Case ReportsThe first case involves a 60-year-old woman with a 7-year history of spontaneous sensations described as a sudden “thump” or “blow” localized to the vertex. Episodes lasted approximately 2 seconds and occurred about once per month. She denied pain, auditory or visual symptoms, dizziness, nausea, aura, or autonomic features. Events occurred in various positions and were not triggered by movement or Valsalva maneuvers. Neurological examination was normal, and there was no relevant medical history.The second case is a 40-year-old woman who experienced brief jolt-like sensations lasting about 3 seconds, localized to a 3-cm area in the left mid-parietal region, often while seated and working. These episodes were immediately followed by a non-painful, warm, heavy sensation extending over a 6–8 cm area, lasting approximately 30 minutes. The phenomenon was non-pulsatile and not associated with nausea, photophobia, or phonophobia. Episodes occurred spontaneously 2–3 times per month over 18 months and were rated as mildly bothersome but not painful.Comment and ConclusionThese presentations do not conform to existing ICHD-3 diagnoses and may represent a benign primary cranial sensory paroxysm. Differential diagnoses include focal sensory epileptic phenomena or peripheral neuropathic events; however, the ultra-brief, stereotyped, non-painful nature and long-term stability favor a benign entity. Recognition of such cases may contribute to improved classification and understanding of non-painful cranial paroxysms.